A Triad-Based Contextualisation Approach for Understanding of a Critical Issue in a Government Investment Agency - Lim, Chia Yean; Muhammad Rafie, Hj. Mohd. Arshad (The Institute of Electrical Engineers of Japan, 2016)
The ability to correctly understand the context and deliver the exact solution for a critical issue as expected by an agency's stakeholders has been a long-standing problem. This research is motivated to assist the stakeholders to better understand a critical issue by looking into the contextualisation aspects. The proposed contextualisation approach comprises three processes namely the context characterisation, context representation, and context interpretation. At the end of a contextualisation process cycle, a set of consistent triad relationships would be derived to represent the current context of a critical issue. From an experiment that has been conducted with a stakeholder, this proposed approach has proven to be able to help the stakeholders to determine the right context to understand a critical issue. Besides, a case study has also been conducted to prove the ease of use, ease of usefulness, and stakeholder's intention to use of the proposed approach. It is believed that once the proposed approach is conducted in many contextualisation process cycles with the help of machine learning systems and advance analytics tools, it could produce a useful set of contexts for any critical issue in making better decision deliberations and insights.